Probing influence of mesophasic transformation on performance of self-emulsifying system: effect of ion - Patil, Sharvil S.; Venugopal, Edakkal; Bhat, Suresh K.; Mahadik, Kakasaheb R.; Paradkar, Anant R. (Molecular Pharmaceutics, 2012)
Self-emulsifying systems are mixtures of oils and surfactants, ideally isotropic, sometimes including cosolvents, which emulsify under conditions of gentle agitation, similar to those which would be encountered in the gastrointestinal tract. The process of self-emulsification has remained the center of attraction for most researchers. Controlled hydration of self-emulsifying systems shows formation of an intermediate gel phase which upon rupture forms an emulsion. Current work was undertaken to understand and explore the microstructural properties of intermediate gel phase which are believed to influence the performance (droplet size) of the final formulation. The effect of additives on microstructural properties of intermediate gel phase has also been investigated. Microstructural elucidation of hydrated samples of intermediate regimes was done by using techniques such as small angle X-ray scattering, differential scanning calorimetry and rheology. Samples from intermediate regimes showed formation of local lamellar structure which swelled with hydration. In the present work, the effect of addition of salt form of naproxen (sodium and potassium) and naproxen (base) on microstructural properties of intermediate regimes was investigated. Systems containing naproxen salts formed larger droplets whereas naproxen base formed smaller ones. Microstructural properties of intermediate lamellar structures were well correlated with performance of the final formulation. The current studies indicate that by controlling the properties of intermediate regimes optimized formulations with desired performance can be tailor-made.
Keywords: emulsion; lamellar structure; liquid crystal; Microstructure; Naproxen; self-emulsifying system